Malaysian Patients’ Expectations of Orthodontic Treatment in Indian Dental Care Set up: A Questionnaire Survey - Ritesh Singla; Nishu Singla; Anuprita Nair (The Scientific World Journal)
Aims and objectives. To access the expectations of orthodontic treatment among Malaysian patients in the Indian dental care setup and to compare the findings between males and females of the study population. Materials and Methods. A cross-sectional study was conducted on 349 Malaysian patients (182 females and 167 males) aged 18–30 years. A questionnaire consisting of ten items developed by Sawyers and Newton was administered to the patients who visited the department of Orthodontics seeking orthodontic treatment. Outcome measures. Descriptive analysis of the responses and comparison of male and female expectations. Results. Most of the patients expected only a check-up/diagnosis/discussion at their initial appointment, anticipated a fixed type of orthodontic treatment, did not prefer extraction/removal of their teeth, thought the treatment to be painful, and can restrict what they could eat or drink. Positive expectations from the patient included better tooth alignment, enhanced smile, improved confidence, and advancement in professional career. At the same time, nearly half of the patients’ assumed speech/mastication does not get affected during the treatment. Moreover, very few patients believed it would be easier to eat/speak/keep their teeth clean after the treatment. Compared to males, more females had significantly anticipated fixed types of orthodontic treatment, thinking the treatment to be painful and restrictive in terms of what they could eat or drink. Most of the females were unsure about the length of the orthodontic treatment and had significantly higher expectations concerning career improvement. Conclusions. To meet the varied expectations of each of the patients, effective communication between the orthodontist and the patient is essential.